2023
DOI: 10.3390/ijms241310589
|View full text |Cite
|
Sign up to set email alerts
|

Rotenone Blocks the Glucocerebrosidase Enzyme and Induces the Accumulation of Lysosomes and Autophagolysosomes Independently of LRRK2 Kinase in HEK-293 Cells

Laura Patricia Perez-Abshana,
Miguel Mendivil-Perez,
Carlos Velez-Pardo
et al.

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder caused by the progressive loss of dopaminergic (DAergic) neurons in the substantia nigra and the intraneuronal presence of Lewy bodies (LBs), composed of aggregates of phosphorylated alpha-synuclein at residue Ser129 (p-Ser129α-Syn). Unfortunately, no curative treatment is available yet. To aggravate matters further, the etiopathogenesis of the disorder is still unresolved. However, the neurotoxin rotenone (ROT) has been implicated in PD. Therefore, it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Second, autophagy was higher in chronic than acute conditions without an apparent increase in the apoptotic marker CC3. Third, it has been demonstrated that ROT not only targets mitochondria but also inhibits the lysosomal glucosylceramidase beta 1 (GBA1) enzyme, leading to the accumulation of lysosomes and autophagosomes independently of apoptosis [31]. Interestingly, a similar result was obtained with the specific inhibitor GBA1 conduritol-B-epoxide [31].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Second, autophagy was higher in chronic than acute conditions without an apparent increase in the apoptotic marker CC3. Third, it has been demonstrated that ROT not only targets mitochondria but also inhibits the lysosomal glucosylceramidase beta 1 (GBA1) enzyme, leading to the accumulation of lysosomes and autophagosomes independently of apoptosis [31]. Interestingly, a similar result was obtained with the specific inhibitor GBA1 conduritol-B-epoxide [31].…”
Section: Discussionmentioning
confidence: 85%
“…Third, it has been demonstrated that ROT not only targets mitochondria but also inhibits the lysosomal glucosylceramidase beta 1 (GBA1) enzyme, leading to the accumulation of lysosomes and autophagosomes independently of apoptosis [31]. Interestingly, a similar result was obtained with the specific inhibitor GBA1 conduritol-B-epoxide [31]. Four, adaptive autophagy (as it may be the case in the ROT paradigm) might not be an important contributing factor to cell death because most probably it mediates cytoprotective rather than cytotoxic effects on DALNs exposed to ROT [72,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation